Visitor Satisfaction at Aan Secret Waterfall Agrotourism - Wirabawa, I Dewa Gede; Mudyani Dewi, Indah (Faculty of Agriculture Udayana University, 2025)
BACKGROUND AND OBJECTIVES: Aan Secret Waterfall Agrotourism offers a peaceful and beautiful rural atmosphere, complemented by picturesque rice fields and a hidden waterfall. Visitor numbers to Aan Secret Waterfall Agrotourism have declined, with 250 visitors in 2023 and 225 visitors in 2024. The decline in visitors is attributed to the emergence of new agrotourism destinations. The objective of this study is to analyze visitor characteristics, determine the level of importance visitors place on the destination, assess the performance of the agrotourism destination, and analyze visitor satisfaction levels. This analysis aims to identify destination attributes that require improvement to enhance the performance of Agrowisata Aan Secret Waterfall. METHODS: Data was collected using questionnaires and then tested for validity and reliability. The data was then analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. FINDINGS: The results show that visitors to Aan Secret Waterfall Agrotourism are predominantly males aged 17-25 years old, with a high school/vocational school education level, an income level of Rp. 1.000.000-Rp. 2.500.000, and residing in Bali. The visitor satisfaction level, analyzed using the Customer Satisfaction Index (CSI), stands at 82.39%. The results of the Importance Performance Analysis (IPA) indicate a high level of alignment between performance and importance, with an average score of 95.55%. CONCLUSION: The high scores obtained reflect visitors' expectations, indicating that the performance level of Agrowisata Aan Secret Waterfall is already satisfactory, resulting in high visitor satisfaction. However, improvements are needed in several areas, including trash bins, road access, promotion through social media platforms, and promotion using banners. These improvements are essential to further enhance visitor satisfaction